A kind of diaphragm binder for new energy vehicle battery and preparation method thereof

Acrylic resin emulsion-type separator adhesive prepared by emulsion polymerization, using the isosorbitol block polymer connected by biomass guar gum and ether bonds, to solve the insufficient bonding strength of existing adhesives under high temperature conditions. and the problem of poor high temperature resistance, higher bonding and high temperature resistance are achieved.

CN119039534BActive Publication Date: 2025-02-07GUANGZHOU FUSIDA CHEM PROD CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411527791.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-07
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

The existing adhesives used for lithium-ion battery separators are insufficient in bonding strength under high temperature conditions, which easily leads to an increase in internal resistance of the separator, affects the battery circulation performance, and lacks high-temperature resistance, which may lead to the fall of the ceramic heat-resistant layer. Impacts battery life.

Method used

The emulsion polymerization method is used to prepare an acrylic emulsion-type septum binder, using biomass guar gum as comonomer, and isosorbide block polymer connected through ether bonds as branching functional agent to form highly branched Space network structure, enhance bonding strength and high temperature resistance.

Benefits of technology

It significantly improves the bonding and high-temperature resistance of the separator adhesive, ensures that the ceramic heat-resistant layer is stable under high temperature conditions, avoids powder loss and shedding, and extends battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119039534B_ABST
    Figure CN119039534B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of adhesives, and discloses a diaphragm adhesive for new energy vehicle batteries and a preparation method thereof. The diaphragm adhesive is prepared by emulsion polymerization using a first functional agent, a second functional agent, a biomass agent and a branching functional agent as copolymers. The addition of biomass guar gum can make the prepared adhesive show higher bonding performance, which is conducive to the stable presence of a ceramic heat-resistant layer on the surface of the diaphragm. The addition of the branching functional agent can make the molecular chain of the adhesive present a highly branched spatial network structure, which can not only enhance the bonding strength of the adhesive, but also the generated ether bonds can also enhance the bonding effect of the adhesive. In addition, isosorbide has a rigid structure, and can introduce a rigid heterocycle into the molecular chain of the adhesive, thereby effectively improving the high temperature resistance of the adhesive.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of adhesives, and in particular to a diaphragm adhesive for new energy vehicle batteries and a preparation method thereof. Background Art

[0002] At present, the environmental problems and energy crisis caused by the drastic consumption of traditional fossil energy are becoming increasingly serious. The development of renewable clean energy to replace traditional fossil energy is undoubtedly an important way to solve this problem. Among them, the application of electric energy is very extensive, and it has gradually replaced traditional fossil energy in the field of automobile drive. At present, most new energy vehicles are generally driven by lithium-ion batteries, and the diaphragm, as an important component of lithium-ion batteries, has a decisive influence on the performance of lithium-ion batteries. Because polyethylene or polypropylene diaphragms have good mechanical properties and high porosity, they are often used to manufacture commercial lithium-ion batteries. However, in actual applications, polyethylene or polypropylene diaphragms shrink severely under high temperature conditions, which may cause battery short circuits and fire accidents, so there are great safety hazards.

[0003] In order to avoid the above problems, the current method is mainly to coat the surface of the diaphragm with a ceramic heat-resistant layer. This method can effectively reduce the shrinkage of the diaphragm under high temperature conditions, and can also effectively improve the wettability of the diaphragm to prevent short circuits caused by lithium dendrite puncture. In order to make the ceramic heat-resistant layer stably exist on the surface of the diaphragm, it is necessary to use a binder for bonding. At present, the binders on the market generally have low bonding strength, easy to fall off, resulting in increased internal resistance of the diaphragm, and affecting the cycle performance of lithium-ion batteries. In addition, since lithium batteries generate heat during use, this causes the battery diaphragm to be at a high operating temperature for a long time. Therefore, the binder used for the diaphragm also needs to have good high temperature resistance to avoid the ceramic heat-resistant layer from falling off and falling due to high temperature aging of the binder, affecting the battery life. Therefore, it is of great significance to develop a diaphragm binder with excellent bonding and high temperature resistance. Summary of the invention

[0004] In order to solve the technical problems mentioned in the background technology, the purpose of the present invention is to provide a diaphragm binder for new energy vehicle batteries and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A diaphragm binder for new energy vehicle batteries is prepared from the following raw materials in parts by weight: 25-35 parts of a first functional agent, 2-5 parts of a second functional agent, 1-3 parts of a biomass agent, 0.5-1.5 parts of a branched functional agent, 0.1-0.5 parts of an initiator, 1-2 parts of an emulsifier, and 30-60 parts of purified water;

[0007] The preparation method of the diaphragm binder comprises the following steps:

[0008] S1. Mix the initiator with one third of purified water to prepare an initiator buffer solution;

[0009] S2, mixing the first functional agent, the second functional agent, the biomass agent, the emulsifier and the remaining two-thirds of purified water, stirring and emulsifying at a stirring rate of 2000-3000 r / min to form a prepolymer emulsion;

[0010] S3, transferring the prepolymer emulsion to a polymerization kettle, introducing nitrogen protection after the addition, gradually raising the temperature to 80-90°C, and then dropping half of the initiator buffer solution into the polymerization kettle, keeping the temperature and stirring for 1-2h to form a prepolymer;

[0011] S4, controlling the temperature to 50-60°C, adding the branching functional agent to the prepolymer, and adding the remaining amount of the initiator buffer solution at the same time, after adding, gradually raising the temperature to 90-100°C, keeping the temperature for 3-6 hours, cooling and discharging the material to obtain a diaphragm adhesive.

[0012] Specifically, an emulsion polymerization method is adopted, with a first functional agent, a second functional agent, a biomass agent, and a branched functional agent as polymerization monomers, and emulsion polymerization is carried out under the initiation of an initiator to prepare an acrylic resin emulsion type diaphragm adhesive.

[0013] As a further embodiment of the present invention, the first functional agent is selected from methyl methacrylate or methyl acrylate; the second functional agent is selected from any one of butyl acrylate, ethyl acrylate or vinyl acetate; the initiator is selected from potassium persulfate or ammonium persulfate; the emulsifier is selected from sodium dodecylbenzene sulfonate or sodium dodecyl sulfonate.

[0014] As a further embodiment of the present invention, the biomass agent is prepared by the following method:

[0015] Guar gum and tetrahydrofuran are mixed and stirred to form a mixed liquid, and then an olefination modifier is added to the mixed liquid, and the mixture is stirred and mixed under nitrogen protection, and then a catalyst is added. After the addition is completed, the temperature is gradually controlled at 60-65°C, and the mixture is kept warm for 3-6 hours under continuous stirring. The mixture is cooled and discharged, and the solid matter is separated to obtain a biomass agent.

[0016] As a further embodiment of the present invention, the olefinic modifier is selected from any one of allyl isocyanate, isocyanoethyl acrylate or isocyanoethyl methacrylate.

[0017] As a further embodiment of the present invention, the catalyst is selected from any one of dibutyltin dilaurate, stannous octoate, dibutyltin diacetate or dibutyltin didodecylsulfide.

[0018] Specifically, the guar gum structure contains active hydroxyl substituents, which can undergo an amine esterification reaction with the isocyanate group in the olefinic modifier structure under the action of a metal tin catalyst, thereby modifying the polymerizable unsaturated olefinic functional group in the olefinic modifier structure in the guar gum molecular chain to produce a guar gum-based biomass agent.

[0019] As a further embodiment of the present invention, the preparation method of the branched functional agent is as follows:

[0020] Isosorbide is added to toluene, mechanically stirred to mix, and then carbonate aqueous solution is added. After the addition, the temperature is controlled to 50-60°C, and mechanically stirred for 1-2 hours. Then, 2,3-dibromopropyl acrylate is added. After the addition, the temperature is further increased to 70-80°C and stirred for 6-9 hours. After the reaction is completed, the solvent is evaporated and removed, and the temperature is cooled and discharged to obtain a branched functional agent. The whole process is carried out under nitrogen protection.

[0021] As a further embodiment of the present invention, the molar ratio of isosorbide to 2,3-dibromopropyl acrylate is 1:0.8-1.

[0022] As a further embodiment of the present invention, the carbonate is selected from potassium carbonate or sodium carbonate.

[0023] As a further embodiment of the present invention, the mass fraction of the carbonate aqueous solution is 15-25%.

[0024] Specifically, in the above technical scheme, carbonate is first used to activate the active hydroxyl substituent in the isosorbide structure, and then a continuous and uninterrupted substitution reaction is carried out with the halogen substituent in the 2,3-dibromopropyl acrylate structure to form a block polymer connected by ether bonds to obtain a branched functional agent. Since the raw material 2,3-dibromopropyl acrylate contains unsaturated olefin groups in its structure, it can undergo free radical polymerization with the first functional agent and other raw materials. The large number of unsaturated olefin functional groups in the branched cross-linking agent structure is utilized to make the acrylate molecular chain produced by the emulsion polymerization reaction have a highly branched structure.

[0025] A diaphragm binder for new energy vehicle batteries is prepared by the above-mentioned preparation method.

[0026] Beneficial effects of the present invention:

[0027] (1) The present invention uses biomass guar gum as a comonomer to participate in the emulsion polymerization process of the diaphragm adhesive, so that the molecular structure of the prepared adhesive contains a biomass guar gum structure. Since guar gum itself has a colloidal structure and contains a large number of oxygen-containing functional groups such as hydroxyl groups in its structure, it can strengthen the interaction with the adhered object by forming hydrogen bonds, thereby showing higher bonding performance, which is conducive to the stable existence of the ceramic heat-resistant layer on the surface of the diaphragm.

[0028] (2) The present invention uses an isosorbide block polymer connected by an ether bond as a branching functional agent. During the emulsion polymerization process of the adhesive, the molecular chain of the adhesive presents a highly branched spatial network structure. This spatial network structure can significantly increase the cohesive energy of the adhesive, which is beneficial to enhancing the bonding strength of the adhesive. Moreover, the generated ether bonds can also improve the bonding effect of the adhesive. In addition, isosorbide has a rigid structure and can introduce rigid heterocycles into the molecular chain of the adhesive, which can not only hinder the movement of the molecular chain of the adhesive, but also make the adhesive show higher stability, thereby effectively improving the high temperature resistance of the adhesive.

[0029] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0031] Figure 1 This is the infrared analysis test diagram of the branched functional agent. DETAILED DESCRIPTION

[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1

[0033] A diaphragm binder for new energy vehicle batteries is prepared from the following raw materials in parts by weight: 25 parts of methyl methacrylate, 2 parts of butyl acrylate, 1 part of biomass agent, 0.5 parts of branching functional agent, 0.1 parts of potassium persulfate, 1 part of sodium dodecylbenzene sulfonate, and 30 parts of purified water;

[0034] The preparation method comprises the following steps:

[0035] S1. Mix potassium persulfate with one-third of purified water to prepare an initiator buffer solution;

[0036] S2, methyl methacrylate, butyl acrylate, biomass agent, sodium dodecylbenzene sulfonate and the remaining two-thirds of purified water are mixed, and stirred and emulsified at a stirring rate of 2500 r / min to form a prepolymer emulsion;

[0037] S3, transferring the prepolymer emulsion to a polymerization kettle, introducing nitrogen protection after the addition, gradually raising the temperature to 80°C, and then dropping half of the initiator buffer solution into the polymerization kettle, keeping the temperature and stirring for 2 hours to form a prepolymer;

[0038] S4, controlling the temperature at 50°C, adding the branching functional agent to the prepolymer, and adding the remaining amount of the initiator buffer solution at the same time, after adding, gradually raising the temperature to 90°C, keeping the temperature for 6 hours, cooling and discharging the material to obtain a diaphragm adhesive. Example 2

[0039] A diaphragm binder for new energy vehicle batteries is prepared from the following raw materials in parts by weight: 30 parts of methyl acrylate, 4 parts of ethyl acrylate, 2 parts of biomass agent, 1 part of branching functional agent, 0.2 parts of ammonium persulfate, 1.5 parts of sodium dodecyl sulfonate, and 50 parts of purified water;

[0040] The preparation method comprises the following steps:

[0041] S1. Mix ammonium persulfate with one-third of purified water to prepare an initiator buffer solution;

[0042] S2, methyl acrylate, ethyl acrylate, biomass agent, sodium dodecyl sulfate and the remaining two-thirds of purified water are mixed, and stirred and emulsified at a stirring rate of 2500 r / min to form a prepolymer emulsion;

[0043] S3, transferring the prepolymer emulsion to a polymerization kettle, introducing nitrogen protection after the addition, gradually raising the temperature to 85°C, and then dropping half of the initiator buffer solution into the polymerization kettle, keeping the temperature and stirring for 1 hour to form a prepolymer;

[0044] S4, controlling the temperature at 50°C, adding the branching functional agent to the prepolymer, and adding the remaining amount of the initiator buffer solution at the same time, after adding, gradually raising the temperature to 95°C, keeping the temperature for 4 hours, cooling and discharging the material to obtain a diaphragm adhesive. Example 3

[0045] A diaphragm binder for new energy vehicle batteries is prepared from the following raw materials in parts by weight: 35 parts of methyl acrylate, 5 parts of vinyl acetate, 3 parts of biomass agent, 1.5 parts of branching functional agent, 0.5 parts of ammonium persulfate, 2 parts of sodium dodecyl sulfonate, and 60 parts of purified water;

[0046] The preparation method comprises the following steps:

[0047] S1. Mix ammonium persulfate with one-third of purified water to prepare an initiator buffer solution;

[0048] S2, methyl acrylate, vinyl acetate, biomass agent, sodium dodecyl sulfonate and the remaining two-thirds of purified water are mixed, and stirred and emulsified at a stirring rate of 3000 r / min to form a prepolymer emulsion;

[0049] S3, transferring the prepolymer emulsion to a polymerization kettle, introducing nitrogen protection after the addition, gradually raising the temperature to 90°C, and then dropping half of the initiator buffer solution into the polymerization kettle, keeping the temperature and stirring for 1 hour to form a prepolymer;

[0050] S4, controlling the temperature at 60°C, adding the branching functional agent to the prepolymer, and adding the remaining amount of the initiator buffer solution at the same time, after adding, gradually raising the temperature to 100°C, keeping the temperature for 3 hours, cooling and discharging the material to obtain a diaphragm adhesive.

[0051] Comparative Example 1

[0052] A diaphragm binder for new energy vehicle batteries is prepared from the following raw materials in parts by weight: 30 parts of methyl acrylate, 4 parts of ethyl acrylate, 1 part of a branching functional agent, 0.2 parts of ammonium persulfate, 1.5 parts of sodium dodecyl sulfonate, and 50 parts of purified water;

[0053] The preparation method comprises the following steps:

[0054] S1. Mix ammonium persulfate with one-third of purified water to prepare an initiator buffer solution;

[0055] S2, methyl acrylate, ethyl acrylate, sodium dodecyl sulfate and the remaining two-thirds of purified water are mixed, and stirred and emulsified at a stirring rate of 2500 r / min to form a prepolymer emulsion;

[0056] S3, transferring the prepolymer emulsion to a polymerization kettle, introducing nitrogen protection after the addition, gradually raising the temperature to 85°C, and then dropping half of the initiator buffer solution into the polymerization kettle, keeping the temperature and stirring for 1 hour to form a prepolymer;

[0057] S4, controlling the temperature at 50°C, adding the branching functional agent to the prepolymer, and adding the remaining amount of the initiator buffer solution at the same time, after adding, gradually raising the temperature to 95°C, keeping the temperature for 4 hours, cooling and discharging the material to obtain a diaphragm adhesive.

[0058] Comparative Example 2

[0059] A diaphragm binder for new energy vehicle batteries is prepared from the following raw materials in parts by weight: 30 parts of methyl acrylate, 4 parts of ethyl acrylate, 2 parts of biomass agent, 0.2 parts of ammonium persulfate, 1.5 parts of sodium dodecyl sulfonate, and 50 parts of purified water;

[0060] The preparation method comprises the following steps:

[0061] S1. Mix ammonium persulfate with one-third of purified water to prepare an initiator buffer solution;

[0062] S2, methyl acrylate, ethyl acrylate, biomass agent, sodium dodecyl sulfate and the remaining two-thirds of purified water are mixed, and stirred and emulsified at a stirring rate of 2500 r / min to form a prepolymer emulsion;

[0063] S3. Transfer the prepolymer emulsion to the polymerization kettle. After the addition, introduce nitrogen protection, gradually increase the temperature to 85°C, then drop the initiator buffer solution into the polymerization kettle, keep warm and stir for 5 hours to obtain the diaphragm adhesive.

[0064] The biomass agent in the above examples and comparative examples was prepared by the following method:

[0065] 1.6 g of guar gum was mixed with tetrahydrofuran and stirred to form a mixed liquid. Then 0.5 g of isocyanoethyl methacrylate was added to the mixed liquid and stirred under nitrogen protection. Then 0.02 g of dibutyltin dilaurate was added. After the addition, the temperature was gradually controlled to 65°C and kept warm for 5 hours under continuous stirring. The temperature was lowered and the material was discharged. The solid matter was separated to obtain a biomass agent.

[0066] The biomass agent was sampled and then subjected to organic element analysis using an XKCHN-700 element analyzer. The analysis results showed that the carbon content of the biomass agent sample was 41.15%, and the nitrogen content was 2.17%, wherein the nitrogen was provided by isocyanoethyl methacrylate.

[0067] The branched functional agents in the above examples and comparative examples were prepared by the following method:

[0068] 0.8 g of isosorbide was added to toluene, and the mixture was mechanically stirred to mix. Then, 1 mL of a 20% sodium carbonate aqueous solution was added. After the addition, the temperature was controlled to 55°C. After mechanical stirring for 2 hours, 1.3 g of 2,3-dibromopropyl acrylate was added. After the addition, the temperature was further increased to 75°C and stirred for 8 hours. After the reaction was completed, the solvent was evaporated and removed, and the temperature was cooled and discharged to obtain a branched functional agent. The whole process was carried out under nitrogen protection.

[0069] Figure 1 This is the infrared analysis test diagram of the branched functional agent. Since the isosorbide used in the above reaction process is excessive, the 3310cm -1 The absorption peak at 3002cm is the characteristic absorption peak of hydroxyl group. -1 The absorption peak at 1737 cm is the characteristic absorption peak of CH on the unsaturated carbon-carbon double bond. -1 The absorption peak at 1042 cm is the characteristic absorption peak of C=O in the ester group. -1 The absorption peak that appears at is the CO characteristic absorption peak of the ether bond.

[0070] Test Case

[0071] 2 g of each binder in Examples 1 to 3 and Comparative Examples 1 to 2 were weighed as test samples, and mixed with 8.5 g of ceramic particles with an average particle size of 0.5 μm, 0.06 g of polyvinyl pyrrolidone, 0.02 g of disodium lauryl polyoxyethylene ether sulfonate, 0.01 g of sodium carboxymethyl cellulose and 20 g of purified water to prepare a binder slurry, which was then evenly coated on the surface of the polyethylene base film in a single-layer coating manner with a coating thickness of 3 μm. After drying and roller pressing, the slurry was uniformly mixed with 8.5 g of ceramic particles with an average particle size of 0.5 μm, 0.06 g of polyvinyl pyrrolidone, 0.02 g of disodium lauryl polyoxyethylene ether sulfonate, 0.01 g of sodium carboxymethyl cellulose and 20 g of purified water to prepare a binder slurry. The slurry was then uniformly coated on the surface of the polyethylene base film in a single-layer coating manner with a coating thickness of 3 μm. Then cut it into 25×200mm test samples, use VHB pressure-sensitive tape to stick on the coating surface of the test sample, fix the tape on the fixture of the tensile machine, fix the edge of the test sample at the other end, peel 150mm in the 180° direction at a tensile speed of 50mm / min, and perform a peel strength test. After the test is completed, take another group of test samples of the same specifications, treat them in a drying oven at 120℃ for 6h, then take them out, and perform a peel strength test again in the same way to evaluate the high temperature resistance of the adhesive;

[0072] The test results are recorded in Table 1:

[0073] Table 1 - Test results

[0074]

[0075] From the analysis of the test results, the adhesive prepared by adding biomass agent and branched functional agent at the same time has more excellent bonding performance, and can still maintain good bonding performance after high temperature treatment, and has good high temperature resistance.

[0076] After removing the biomass agent, it can be clearly observed that the bonding performance of the binder has decreased significantly, but the high temperature resistance performance is still acceptable. After removing the branching functional agent, the ether bonds in the molecular structure of the binder are greatly reduced, and the cross-linking density is reduced, so the bonding performance also decreases significantly. At the same time, the stable rigid structure of isosorbide is lost, resulting in a significant decrease in high temperature resistance.

[0077] Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enable any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.

Claims

1. A method for preparing a diaphragm binder for new energy vehicle batteries, characterized in that: The method is prepared from the following raw materials in parts by weight: 25-35 parts of a first functional agent, 2-5 parts of a second functional agent, 1-3 parts of a biomass agent, 0.5-1.5 parts of a branching functional agent, 0.1-0.5 parts of an initiator, 1-2 parts of an emulsifier, and 30-60 parts of purified water; The preparation method comprises the following steps: S1. Mix the initiator with one third of purified water to prepare an initiator buffer solution; S2, mixing the first functional agent, the second functional agent, the biomass agent, the emulsifier and the remaining two-thirds of purified water, stirring and emulsifying at a stirring rate of 2000-3000 r / min to form a prepolymer emulsion; S3, transferring the prepolymer emulsion to a polymerization kettle, introducing nitrogen protection after the addition, gradually raising the temperature to 80-90°C, and then dropping half of the initiator buffer solution into the polymerization kettle, keeping the temperature and stirring for 1-2h to form a prepolymer; S4, controlling the temperature to 50-60°C, adding the branching functional agent to the prepolymer, and adding the remaining amount of the initiator buffer solution, after adding, gradually raising the temperature to 90-100°C, keeping the temperature for 3-6 hours, cooling and discharging the material to obtain a diaphragm adhesive; The first functional agent is selected from methyl methacrylate or methyl acrylate; the second functional agent is selected from any one of butyl acrylate, ethyl acrylate or vinyl acetate; The biomass agent is guar gum containing unsaturated olefin functional groups in its structure; The branching functional agent is prepared by reacting isosorbide and 2,3-dibromopropyl acrylate as reactants; The molar ratio of isosorbide to 2,3-dibromopropyl acrylate is 1:0.8-1.

2. The method for preparing a diaphragm binder for new energy vehicle batteries according to claim 1, characterized in that: The initiator is selected from potassium persulfate or ammonium persulfate; the emulsifier is selected from sodium dodecylbenzene sulfonate or sodium dodecyl sulfonate.

3. The method for preparing a diaphragm binder for new energy vehicle batteries according to claim 1, characterized in that: The biomass agent is prepared by the following method: Guar gum and tetrahydrofuran are mixed and stirred to form a mixed liquid, and then an olefination modifier is added to the mixed liquid, and the mixture is stirred and mixed under nitrogen protection, and then a catalyst is added. After the addition is completed, the temperature is gradually controlled at 60-65°C, and the mixture is kept warm for 3-6 hours under continuous stirring. The mixture is cooled and discharged, and the solid matter is separated to obtain a biomass agent.

4. The method for preparing a diaphragm binder for new energy vehicle batteries according to claim 3, characterized in that: The olefinic modifier is selected from any one of allyl isocyanate, isocyanoethyl acrylate or isocyanoethyl methacrylate.

5. The method for preparing a diaphragm binder for new energy vehicle batteries according to claim 3, characterized in that: The catalyst is selected from any one of dibutyltin dilaurate, stannous octoate, dibutyltin diacetate or dibutyltin didodecylsulfide.

6. The method for preparing a diaphragm binder for new energy vehicle batteries according to claim 1, characterized in that: The preparation method of the branched functional agent is as follows: Isosorbide is added to toluene, mechanically stirred to mix, and then carbonate aqueous solution is added. After the addition, the temperature is controlled to 50-60°C, and mechanically stirred for 1-2 hours. Then, 2,3-dibromopropyl acrylate is added. After the addition, the temperature is further increased to 70-80°C and stirred for 6-9 hours. After the reaction is completed, the solvent is evaporated and removed, and the temperature is cooled and discharged to obtain a branched functional agent. The whole process is carried out under nitrogen protection.

7. The method for preparing a diaphragm binder for new energy vehicle batteries according to claim 6, characterized in that: The carbonate is selected from potassium carbonate or sodium carbonate.

8. The method for preparing a diaphragm binder for new energy vehicle batteries according to claim 6, characterized in that: The mass fraction of the carbonate aqueous solution is 15-25%.

9. A membrane binder for new energy vehicle batteries, characterized in that: The method is prepared according to claim 1.

Citation Information

Patent Citations

  • Guar gum adhesive and preparation method thereof

    CN107057615A

  • Lithium battery negative electrode binder and preparation method thereof

    CN118027860A